Mecanismos de descarga en gases en la región de los subnanosegundos. - D´Alesio, J. T.; Lanza, H. (Comisión Nacional de Energía Atómica (Argentina), 1968)
Fil: D´Alesio, J. T. Comisión Nacional de Energía Atómica; Argentina